Assessment of minimum clinically important difference in symptoms and functionality of Japanese patients with major depressive disorder following inadequate response to antidepressants: a post hoc analysis of the long-term study of brexpiprazole augmentation therapy in Japanese patients with major depressive disorder - Hori, Hikaru; Shiosakai, Masako; Shibasaki, Yoshiyuki; Yamato, Kentaro; Zhang, Yilong (Frontiers in Psychiatry, 2025)
Background and objectivesThe aim of this study was to apply the minimum clinically important difference (MCID) concept to clinical results for Japanese patients with major depressive disorder following inadequate response to antidepressants, and to explore the disparity in what physicians and patients considered important in the treatment of depression.MethodsThe original study was a 52-week, open-label, multicenter study on the administration of 2 mg/d of brexpiprazole as adjunctive therapy for patients with major depressive disorder. Here, we conducted a post hoc analysis to determine the MCID in Montgomery–Åsberg Depression Rating Scale (MADRS), Sheehan Disability Scale (SDS), and EQ-5D-5L-derived utility score. We compared the area under the curve (AUC) and correlation coefficients for the MADRS, SDS, and utility scores between the physicians’ and patients’ responses.ResultsThe MCIDs for this patient group were 4.89–4.94 for the MADRS score, 31.15–35.10% for the MADRS improvement rate, 0.69–2.14 for the SDS score, and 0.045–0.195 for the utility score. The MCIDs for the SDS and utility scores derived from the patient-perspective anchor were almost twice as high as those from the physician-perspective anchor. The utility score had the highest AUC and correlation coefficient for the patient-perspective anchor, while the MADRS score did for the physician-perspective anchor.ConclusionsThe MCIDs for the MADRS, SDS, and EQ-5D-5L -derived utility scores were estimated. Physicians focus more on depressive symptoms and prioritize symptom severity over improvements in functionality and activities of daily life, in contrast to patients, who prioritize such improvements.